Enabling the Business of Agriculture 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Enabling the Business of Agriculture (EBA) 2017, the third report in the EBA series, offers insights into how laws and regulations affect private sector development for agribusinesses, including producer organizations and other agricultural entrepreneurs. Globally comparable data and scored indicators encourage regulations that ensure safety and quality of agricultural inputs, goods and services but are not too costly or burdensome.